Rancangan Mesin Pembelah Buah Pinang Dengan Dua Mata Potong - Rodika Rodika; Tuparjono Tuparjono; Budi Otomo; Riska Ade Febryani (Manutech : Jurnal Teknologi Manufaktur, 2018)
Betel nut palm plant is one of the many benefits and efficacy, especially seeds. Areca nuts are widely used as the main raw material in the process of making drugs, cosmetics, slimming, snacks, sweets, and coffee. Betel nut processing into betel nut is still constrained by the tool is still modest, are still using wood beams repose knife to split betel nut into two parts. To overcome these problems needed betel nut splitter machine with a capacity of 250 kg / h. This engine design is expected to help farmers during the process of betel nut processing into dried betel nut. The working principle of betel nut splitter machine originated from an electric motor that produces rotation is forwarded to the reducer and to the cutting blade associated with two gears. Betel nut is inserted through the insertion funnel towards the rotor has 4 channels / trench, and rotor spinning and crashing betel nut rotating blades reversed so the rotor besidesbetel nut split into two parts. Shaft rotation speed at the eye-piece and carrier rotor shaft is 9.32 rpm, the rotation speed is obtained from the ratio gearbox and pulley on the engine splitter ratio. With the machine is expected to help farmers to cultivate betel nut, so the work is lighter, faster and may prevent accidents. Shaft rotation speed at the eye-piece and carrier rotor shaft is 9.32 rpm, the rotation speed is obtained from the ratio gearbox and pulley on the engine splitter ratio. With the machine is expected to help farmers to cultivate betel nut, so the work is lighter, faster and may prevent accidents. Shaft rotation speed at the eye-piece and carrier rotor shaft is 9.32 rpm, the rotation speed is obtained from the ratio gearbox and pulley on the engine splitter ratio. With the machine is expected to help farmers to cultivate betel nut, so the work is lighter, faster and may prevent accidents.